Respecting Aboriginal Parents’ Involvement in their Children’s Learning - Valerie Harwood; Nyssa Murray (Educação & Realidade, 2020)
In Australia (and arguably in many other countries) parent involvement in their child’s learning is dominated by Western notions of learning, education, pedagogy and knowledge. We discuss the application of a critical anthropology of education angle to these dominant discourses and methodological resources that encourage us to be in the field, to take time, and to, with critical reflexivity, listen and learn. We describe how we worked to create an Aboriginal Guided approach and drew on Aboriginal Research Protocols to maintain a steady and sharp emphasis on our practice as researchers.